Muhammadiyah student association characteristic behavior in educational perspective of Ahmad Dahlan - Ikfi Muallifa Izzati; Miftahuddin Miftahuddin; Aman Aman (Journal of Education and Learning (EduLearn), 2021)
This study aimed to see Ahmad Dahlan's concept of educational thought and Ahmad Dahlan's concept of education in ordering Muhammadiyah student association (IPM) character. This study used a descriptive narrative qualitative research. The research was conducted at Muhammadiyah Kalibening Senior High School, Banjarnegara Regency. The research process was carried out using interview techniques, observation and documentation with data triangulation analysis techniques. The research analysis found that IPM activities lead to Ahmad Dahlan's educational thinking which can form disciplinary attitudes, responsibility, and have broad insights. IPM activities in this school are included in the school curriculum. Students who join the IPM will try to be introspective and discipline themselves in worship and social interactions. The activities of the Muhammadiyah Student Association are implemented in the applicable school curriculum.